Implementation of a workbench platform for the management of smart contracts in BlockChain nodes on Azure Cloud - Daniel-Martínez, Wendy; Santana-Valadez, Luis Alejandro; Zamudio-García, Víctor Manuel; Hernández-Pérez, Faride (Revista Tecnologías de la Información, 2022)
Objectives: Analyze, design and build backend components (web API, XML web service and database) and frontend (website) with Microsoft technology that allow the integration of a functional workbench platform to automate the launch of compiled smart contracts in blockchain nodes hosted in Azure Cloud so that they can be used by companies in general. Methodology: The SCRUM methodology was applied for the agile development of the technological products of the backend and frontend, because it adapted very well to the nature of this research, since in each iteration there was always an update of the tools, programming components, testing and configuring services to achieve goals. Contribution: It is shown that the development platform integrated by the solidity language, Azure cloud blockchain, the Visual Studio .Net IDE and the SQL Server database manager allowed to design and build a blockchain workbench platform easily exploitable by companies to validate their processes and generate transparency in the handling of their information.